THE DEVELOPMENT OF AUDIO VISUAL EFL MATERIAL FOR TEACHING TENSES, SYNONYMS AND ANTONYM IN 2NDARY SCHOOL - Najwa Rizki Amalia; Syarifah Soraya, Ciraenda Caenovea, Muhammad Alief Raihan Ramadhan (International Journal of Teaching and Learning, 2026)
Teaching English as a Foreign Language (EFL) at the secondary school level faces various challenges, including low student motivation and difficulties in understanding abstract concepts such as tenses, synonyms, and antonyms. This study aims to develop interactive audio-visual learning media to improve students' comprehension and motivation in learning. The research employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to systematically design media that integrates elements such as animations, simulations, and interactive quizzes. The results of this study demonstrate that interactive audio-visual media significantly enhance student engagement. This method is particularly eflective for teaching tenses, synonyms, and antonyms.. Based on a thorough literature review, the use of such media significantly enhances learning outcomes and increases student involvement in the learning process. The incorporation of multimedia learning theories, such as Mayer’s Cognitive Theory of Multimedia Learning and Constructivist Theory, ensures that the media developed addresses the complex and abstract nature of EFL topics, fostering deeper and more practical understanding for secondary school students. This research reaffirms the relevance and eflectiveness of audio- visual media in supporting EFL learning success, providing innovative methods to overcome challenges in teaching abstract concepts to students.